MAJELIS TAFSIR AL-QUR’AN PERWAKILAN DELI SERDANG MENURUT PANDANGAN MASYARAKAT DESA LAUT DENDANG - Muzakkir Muzakkir; Muhammad Hidayat; Presty Zulianingsih (UIN Sumatera Utara Medan, 2022)
In general, the insight and knowledge of Muslims towards Islam is still relatively low. The role of religious leaders who serve as role models for Muslims is sometimes still not contributing to the community. Such conditions make the Indonesian people who adhere to Islam do not have perfect Islamic knowledge. In order to pandangand to this, several organizations, foundations and even movements based on Islam have emerged with the aim of improving religious attitudes in society. One example of a foundation that has this goal is the Alqur'an Tafsir Council. This research is a qualitative research which is classified as field research which involves observation and interviews with several informants. It is also supported by data obtained by the office of the head of Laut Dendang village and as supporting literature in this study also using books, journals or others that are in accordance with the title of the study. The results of the research revealed that the pandanganse of the people of Laut Dendang Village to the Deli Serdang Representative Council of the Alqur'an or MTA was good and its presence was very welcome by the community and even the people were happy because it could provide changes to the people in Laut Dendang Village both in terms of religion, social economy and so on and if there are negative comments from some people, it's just a misunderstanding from people who don't know MTA fully. For this reason, it is necessary to have a dialogue or discussion with the Qur'anic Interpretation Council so that we can prove the negative information or issues.